The Influence of Academic Supervision and Professional Competence on Teacher Performance Through Work Commitment : ENGLISH - Wulan Devinta Ahmanda; Rihab Wit Daryono (Jurnal Educative: Journal of Educational Studies, 2024)
The background of this study is based on the importance of the quality of education influenced by teacher performance, which is often influenced by supervision support and competency development. This study aims to analyze the effect of academic supervision and professional competence on teacher performance at Madrasah Tsanawiyah, with work commitment as a mediator. The research method used is quantitative, with data collection through questionnaires distributed to 60 teachers, principals, and education personnel at MTs Al Islam Joresan Ponorogo. The sampling technique used is probability sampling. Data analysis was carried out using PLS-SEM, chosen because of its ability to test complex relationships between variables and facilitate structural modeling. The study results indicate that academic supervision and professional competence significantly affect teacher performance, which is mediated by work commitment. This finding indicates that improvements in supervision and professional competence can increase teacher work commitment, which in turn contributes to improving their performance. The implications of this study emphasize the need to develop a more structured academic supervision program and ongoing professional competence training to improve the quality of education. The contribution of this research lies in enriching the literature on the relationship between supervision, competence, and teacher performance, as well as providing insight for policymakers in formulating strategies to improve the quality of education.